Unraveling the Complexity to Observe Associations Between Welfare Indicators and Hair Cortisol Concentration in Dairy Calves - Tamminen, Lena-Mari; Keeling, Linda J.; Svensson, Anna; Briot, Laurie; Emanuelson, Ulf (Frontiers in Animal Science, 2021)
Using levels of the stress hormone cortisol as an indicator for welfare is a common, but debated, practice. In this observational study hair cortisol concentration of samples from 196 dairy calves from 7 to 302 days of age collected from 12 Swedish farms were determined using a commercially available ELISA. An assessment of animal welfare, assessed using animal-based indicators, was performed on the day of sampling. First, methodological factors with the potential to impact hair cortisol concentration and the effect of age were analyzed using generalized additive models. This revealed a significant peak in hair cortisol in young calves (around 50 days of age) and an association between fecal contamination of hair samples and the level of cortisol extracted. Secondly, associations between welfare indicators and hair cortisol concentration were explored using cluster analysis and regularized regression. The results show a complex pattern, possibly related to different coping styles of the calves, and indicators of poor welfare were associated with both increased and decreased hair cortisol levels. High cortisol levels were associated with potential indicators of competition, while low cortisol levels were associated with signs of poor health or a poor environment. When running the regularized regression analysis without the contaminated hair samples and with the contaminated samples (including a contamination score) the results did not change, indicating that it may be possible to use a contamination score to correct for contamination.